2015
DOI: 10.1039/c4ta04570j
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of Li distribution in Li7−xHxLa3Zr2O12garnets

Abstract: We present a NMR investigation of 6Li7−xHxLa3Zr2O12 (0 ≤ x ≤ 5) garnets to study the distribution of Li ions. The facile H+/Li+ exchange alters the relative population of Li sites, and allows the identification of 3 different bands ascribed to Li in different environments. Variable temperature measurements indicated the presence of dynamic processes between octahedral and tetrahedral Li sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 51 publications
5
36
0
Order By: Relevance
“…Attempts were also made to perform a structural refinement using the I 4̅3 d model, which was recently reported for protonated Li oxide garnets and LLZO garnets stabilized with certain cations such as Ga 3+ and Fe 3+ . 40,4447 As the characteristic 310 reflection of space group I 4̅3 d , which appears at d = 4.10 Å (2θ = 21.6°) for LLZO garnets with a unit-cell parameter of 12.97 Å, would shift to larger d values due to the increasing unit-cell parameters of LLZBO, it might be possible that the additional reflection at d = 4.16 Å (2θ = 21.35°) is related to the phase transformation to the I 4̅3 d space group. Rietveld refinement showed that, even for strongly protonated LLZBO samples with large unit-cell parameters of 13.08 Å, this characteristic 310 reflection of space group I 4̅3 d would be located at d = 4.138 Å (2θ = 21.45°).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts were also made to perform a structural refinement using the I 4̅3 d model, which was recently reported for protonated Li oxide garnets and LLZO garnets stabilized with certain cations such as Ga 3+ and Fe 3+ . 40,4447 As the characteristic 310 reflection of space group I 4̅3 d , which appears at d = 4.10 Å (2θ = 21.6°) for LLZO garnets with a unit-cell parameter of 12.97 Å, would shift to larger d values due to the increasing unit-cell parameters of LLZBO, it might be possible that the additional reflection at d = 4.16 Å (2θ = 21.35°) is related to the phase transformation to the I 4̅3 d space group. Rietveld refinement showed that, even for strongly protonated LLZBO samples with large unit-cell parameters of 13.08 Å, this characteristic 310 reflection of space group I 4̅3 d would be located at d = 4.138 Å (2θ = 21.45°).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reporting SG I -43 d for Li-oxide garnets correlated this phase transformation with a protonation process. 40,48 As our samples were characterized immediately after the final calcination step, we exclude a phase transformation due to hydration caused by humidity from exposure to air as supposed by Larraz et al for pure LLZO from I 4 1 / acd to Ia -3 d . 49 Recently, Larraz et al documented some additional weak reflections for pure LLZO that was stored for three years, washed, and then heated to 300 °C that cannot be explained using SG Ia -3 d .…”
Section: Discussionmentioning
confidence: 99%
“…49 Recently, Larraz et al documented some additional weak reflections for pure LLZO that was stored for three years, washed, and then heated to 300 °C that cannot be explained using SG Ia -3 d . 48 They already assumed that these reflections might be related to SG I -43 d . In contrast to this, Ma et al did not observe any phase transformation for cubic LLZO exposed to aqueous solutions and suggested that LLZO with SG Ia -3 d is relatively stable, even at very high Li + /H + exchange rates of 63.6%, which affected almost solely 4-fold-coordinated Li at the 96 h position.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure parallel surfaces, the discs were ground with sand paper (400 grit Black ice dry/wet sand paper, Norton Corporation, USA) using a lapping fixture (Model 900; Southbay Technologies, San Clemente, CA, USA) (Kim et al, 2016). The discs were stored in an argonfilled glove box (<1 ppm O2, <1 ppm H2O) to minimize surface contamination (Jin and McGinn, 2013;Larraz et al, 2015).…”
Section: Densificationmentioning
confidence: 99%
“…To remove the Li2CO3 and LiOH surface contamination layers (Jin and McGinn, 2013;Larraz et al, 2015), the hot-pressed LLZNO and LLZTO discs were dry polished with sand paper on a glass plate in the argon-filled glove box. Li foil (Alfa Aesar) was scraped using a spatula to remove the oxide surface layer.…”
Section: Characterizationmentioning
confidence: 99%